EFFECT OF MUSCLE ENERGY TECHNIQUE AND CONVENTIONAL APPROACH ON FUNCTIONAL OUTCOMES IN TOTAL KNEE ARTHROPLASTY-A COMPARATIVE STUDY - Shinde, Sandeep Babasaheb (International Journal of Psychosocial Rehabilitation, 2020)
Background:The increasing use of Total Knee Arthroplasty(TKA)has raised several public and clinical policy issues. In post-operative period, acute surgical pain is manifested and is most intense during the first 2 weeks. Disruption and inflammation of the peri-articular soft tissues present as a soft tissue stiffness pattern that differs from the pro-operative rigid stiffness of advanced arthrosis.It is well established that pain and joint swelling limit the function of hip and knee muscles.Quality physiotherapy interventions to address muscular dysfunction for TKA is an essential aspect which is in need to be concentrated. The main emphasis should be given to improve the quality of knee function after TKA and make the patient independent.Objectives:To study and find the effect of Muscle energy technique on functional outcomes in TKA patients.To compare the effect of Muscle energy technique technique along with conventional exercises and conventional exercises alone for TKA rehabilitation.Methods:A total number of 20 subjects were randomly allocated into 2 groups (10 in each group) with simple random sampling method. Group A (experimental group) included 7 males and 3 females, treated with METS along with conventional exercises and group B (control group) included 7 males and 3 females, treated with conventional exercises for TKA rehabilitation. Results:Among the different sections of WOMAC scale significant improvement were seen in group A then group B in pain intensity ( t = 2.746, p= 0.0133 ), stiffness ( t = 3.497, p= 0.0026 ), and physical functions ( t = 4.771, p= 0.0002 ).ROM also showed significant difference in group A compared to group B, in both flexion ROM ( t = 6.026, p= <0.001 ) and extension lag ROM (t=0.3795, p= 0.7088).Muscle strength also showed significant improvement in group A compared to group B, in both flexor strength (t=2.178, p= 0.0429) and extensor group (t= 5.109, p=<0.001). Conclusion: This study after statistical analysis concluded that METS along with conventional exercises has better outcome results than conventional exercises alone on all 3 components of WOMAC scale, ROM and muscle strength in TKA rehabilitation